Population, Wealth, and Economic Growth in the Asia and Pacific Region - Andrew Mason; Sang-Hyop Lee (Asian Development Bank (ADB), 2011)
We explore how demographic changes in the Asia and Pacific region are likely to influence economic growth and other features of the regional economy. While many low-income countries in the region will continue to experience a demographic dividend, over time population aging could drag on economic growth, especially in East Asia. A second potential problem from population aging is the strain on public transfer systems the effects of which, although smaller than those in Europe, Japan, or Latin America, will still be large. Countering these problems, however, population aging will lead to substantial capital deepening, an effect of the second demographic dividend. Given current patterns of old-age consumption, production, and transfers, the total demand for pension assets will increase very substantially over the coming decades. Under these circumstances, aging should not depress savings rates. Capital deepening and high standards of living are attainable despite significant population aging.
hdl:11540/2004
Keywords: 330; Bevölkerungsentwicklung; Bevölkerungsstruktur; Alternde Bevölkerung; Wirkungsanalyse; Wirtschaftswachstum; Asiatisch-pazifischer Raum